Evaluasi Alat Pemadam Api Ringan Berdasarkan Permenakertrans Nomor 4 Tahun 1980 di UD. Riwood Sidoarjo - Fitria, Sindy Nur; Ratriwardhani, Ratna Ayu; Sofia, Rizka Amirul; Wasillah, Farikhatul; Abadi, Ongky Putra; Rhomadhoni, Muslikha Nourma (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Occupational Safety and Health are very important things to implement in the work environment to protect the risk of accidents. A light fire extinguisher (APAR) is a tool used to control fires. Not all companies provide fire extinguishers, even though this tool is very important as a lifesaver if a fire occurs so that the fire does not spread. The wood industry is one of the largest industries in Indonesia thanks to its abundant natural resources. Pallet wood factory is a company engaged in wood production producing pallet wood products. Problems that occur in the UD industry. Ri Wood lacks awareness about occupational safety and health, one of which is the provision of inappropriate APARs and inappropriate maintenance of APARs. By conducting observations using qualitative methods through data collection, interviews and documentation. And from the results of the calculations that have been carried out, we strongly recommend that the company increase the maintenance and provision of APARs in accordance with Permenakertrans Number 4 of 1980, around five APARs for a total of six APARs. Because every production process has the potential for fire.